2021
DOI: 10.1371/journal.pntd.0009285
|View full text |Cite
|
Sign up to set email alerts
|

Community-based Guinea worm surveillance in Chad: Evaluating a system at the intersection of human and animal disease

Abstract: Background Guinea worm is a debilitating parasitic infection targeted for eradication. Annual human cases have dropped from approximately 3,500,000 in 1986 to 54 in 2019. Recent identification of canine cases in Chad threatens progress, and therefore detection, prevention, and containment of canine cases is a priority. We investigated associations between disease knowledge, community engagement, and canine cases in Chad to identify opportunities to improve active surveillance. Methods We surveyed 627 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A 2019 CGWEP surveillance system evaluation found that the frequency of volunteer visits to households was varied despite program guidance that requires that volunteer visits are to be conducted on a daily basis. 42 Improved supervision and volunteer training and consistent application of program standards throughout different times of year have been identified as future priorities for the CGWEP. 42 Until full control of the zoonotic reservoir(s) is achieved in Chad, renewed transmission to humans will likely remain a risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2019 CGWEP surveillance system evaluation found that the frequency of volunteer visits to households was varied despite program guidance that requires that volunteer visits are to be conducted on a daily basis. 42 Improved supervision and volunteer training and consistent application of program standards throughout different times of year have been identified as future priorities for the CGWEP. 42 Until full control of the zoonotic reservoir(s) is achieved in Chad, renewed transmission to humans will likely remain a risk.…”
Section: Discussionmentioning
confidence: 99%
“…42 Improved supervision and volunteer training and consistent application of program standards throughout different times of year have been identified as future priorities for the CGWEP. 42 Until full control of the zoonotic reservoir(s) is achieved in Chad, renewed transmission to humans will likely remain a risk. This is further complicated by the additional difficulty of detecting and containing infections in mobile groups of people, and by extension their dogs, underscoring the need for a multipronged approach to surveillance and control of Guinea worm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation resulted in identification of system level problems and potential solutions. Although informatics assessments have been conducted on macrolevels for infectious disease [39] and surveillance evaluations performed for Guinea worm disease [4,20,40], our approach is novel in that we assessed the information system from the surveillance need, data management, and data use perspectives for Guinea worm disease. The framework we used here could be adapted by other programs looking to assess their information systems to support surveillance and programmatic needs.…”
Section: Discussionmentioning
confidence: 99%
“…To address the data and information system-related challenges, the Chad Ministry of Public Health and National Solidarity (MoPH) and The Carter Center requested informatics assistance from the Centers for Disease Control and Prevention (CDC) in the form of an "Info-Aid," a mechanism that allows Public Health Informatics Fellows (CDC's "data detectives") to provide short-term technical assistance in the event of an urgent public health need for applied information science and technology [19]. Although a previous, rigorous surveillance evaluation had been conducted [20], it was determined that an additional assessment would be needed specifically to address informatics needs.…”
Section: Objectivementioning
confidence: 99%